Production of a Complementary Food: Influence of Cowpea Soaking Time on the Nutritional, Antinutritional, and Antioxidant Properties of the Cassava-Cowpea-Orange-Fleshed Potato Blends. (28th October 2020) - Olaniran, Abiola Folakemi; Okonkwo, Clinton Emeka; Osemwegie, Omorefosa Osarenkhoe; Iranloye, Yetunde Mary; Afolabi, Yemisi Tokunbo; Alejolowo, Omokolade Oluwaseyi; Nwonuma, Charles Obiora; Badejo, Toluwanimi Esther
Abstract : Soaking and incorporation of legumes for fortification are essential to a complementary food production process. Cassava, orange-fleshed potato, and cowpeas are sustainably cheap, locally available, and underutilized for food biofortification. This study investigated the effect of cowpea soaking time (3, 6, and 9 h) on different composition ratios of cassava, cowpea, and orange-fleshed sweet potato (CCP) blends (50 : 40 : 10 (EC), 50 : 30 : 20 (FC), 50 : 20 : 30 (GC), and 50 : 50 : 0 (HC)). Each blend was assayed for pH, antinutrient, antioxidant, and proximate contents. Results obtained showed that the CCP blends were significantly influenced by the length of cowpea soaking. Moisture and fiber content decreased significantly (P ≤ 0.05 ) with increased steeping time (3 to 9 h) for the cassava-cowpea-OFSP blends. The blends were significantly different (P ≤ 0.05 ) in terms of their protein, fiber, fat, ash, and carbohydrate contents. The moisture content of the EC blend was significantly different from only FC and HC blends, respectively. Six (6) hours of soaking showed no significant difference in the nutritional composition of the flour samples compared with 9 hours. The soaking length optimizes the health and nutrient-promoting factors in the various blend samples while also reaffirming cowpeas as a viable biofortification option for use in complementary food production.